Usability Evaluation and Solution Design Improvement of OCTO Friends as Banking Referral Application - Utami, Aisyah Nurlita; Santoso, Harry Budi (AI Society & STMIK Indonesia, 2024)
OCTO Friends application was developed to allow customers to directly participate in banking product referral program, has not met expectations and targets. Only 10.6% of the 39,105 members actively provided referrals, and business conversion rate was only 10% of the target. This study aims to evaluate the application's usability and generate recommendations for interface design improvement. A mixed methods research approach was used, including quantitative research through user needs questionnaires and System Usability Scale (SUS), along with qualitative research through in-depth interviews and usability testing. Data collection through questionnaires involved 104 respondents, resulting in a list of user needs and SUS score of 66. The results showed that OCTO Friends is requires some improvements. In-depth interviews and usability testing for six main functions led to 46 interface design improvements, especially improvements in referral data input, follow-up referral, and incentive information functions as these are primary functions of referral application.